Fatores associados com a regressão da hipertrofia esquerda em diálise e impacto com mortalidade cardiovascular - Kochi, Ana Claudia [UNESP] (2014)
Once started dialysis, the survival of patients with chronic kidney disease is directly related to cardiovascular changes, as following: left ventricular hypertrophy, myocardial infarction, stroke, cardiac arrhythmias and hypertension. Among these changes left ventricular hypertrophy is a common and powerful risk factor. In this way, reversal of left ventricular hypertrophy has potential to interfere positively with the survival of patients with renal disease, both for cardiovascular causes and for overall mortality. The present study aimed to evaluate the influence of regression of cardiac hypertrophy in cardiovascular mortality in dialysis patients and analyze the influence of clinical variables on the regression of left ventricular hypertrophy. Chronic kidney diseases patíents, aged over 18 years were analyzed, on hemodialysis for at least two months before the initial evaluation, from June 2000 to December 2008, and followed until 2012 in the hemodialysis service at the University Hospital of Botucatu-UNESP. The patients must have two echocardiograms. Were excluded patients with evidence of ventricular dyskinesia in echocardiogram, moderate or severe valvular disease, echocardiography with unsatisfactory technical quality; patients with cardiomyopathies due to causes other than hypertension or uremic; patients whose disease has a low life expectancy, which are: neoplasms and liver cirrhosis, and those undergoing kidney transplantation between the ftrst and second assessment. The patients were divided into two groups: those that maintained or increased the cardiac ventricular mass, and those that have reduced cardiac ventricular mass during follow-up. Multiple Cox regression was performed to evaluate the influence of reversal of left ventricular hypertrophy on mortality from cardiovascular causes. Over 6 years of follow-up, the survival curves of the two groups distanced themselves in a statistically signiftcant way. Reversal of left ...